Polyadenylation as a target for anti-inflammatory drugs - Radhi, Masar (2019)
Polyadenylation is a universal step in the maturation of all eukaryotic mRNAs except histone mRNAs. Despite being universal, previous experiments have implicated it in the regulation of inflammatory response. An inflammatory system using RAW 264.7 murine macrophage cells was established with bacterial lipopolysaccharide (LPS) used as a stimulus. The inflammatory response is a tightly regulated reaction. It involves both signals that initiate and maintain inflammation and signals that shut the process down. An imbalance between the two signals leaves inflammation unchecked, resulting in cellular and tissue damage. Macrophages are widely-distributed innate immune cells and considered as a major component of the mononuclear phagocyte system that consists of closely related cells of bone marrow origin, including blood monocytes, and tissue resident macrophages. Stimulation of macrophages with LPS results in the production of various cytokines (e.g., TNF-α and IL-1β) and inflammatory effectors (e.g., prostanoids, leukotrienes, and nitric oxide). NF-ĸB is the master regulator of the inflammatory response in macrophages. Upon phosphorylation and subsequent degradation of its inhibitor, IĸBα, the liberated NF-κB dimer translocates to the nucleus and switches on the transcription of genes controlling inflammation, immunity, cell proliferation and apoptosis. PI3K/Akt/mTOR signal transduction pathway has been implicated in the regulation of both innate and adaptive immunity. Cordycepin is one of the major bioactive substances produced by Cordyceps militaris, a parasitic fungus used in the traditional Chinese medicine. It is an adenosine analogue that lacks the 3’ hydroxyl group, and therefore functions as a chain terminator if phosphorylated and incorporated into a growing polyadenylation reaction. Cordycepin was shown to possess an anti-inflammatory effect both in cell culture and in animal models of inflammation associated-disorders. The role of cordycepin in regulating the expression of inflammatory genes in macrophages, essential transcription factors as well as its involvement in PI3K/Akt/mTOR signal transduction pathway were studied. Cordycepin was shown to have fast anti-inflammatory effect and it is likely to be primary in nature. Cordycepin was also shown to repress the inflammatory gene expression at the transcriptional level. It was found to interfere with NF-ĸB signalling. It reduced the nuclear localization of p65 in macrophages, but this effect was not IĸBα degradation-dependent. Furthermore, cordycepin has shown inhibitory effect on PI3K/Akt/mTOR signal transduction pathway by reducing the phosphorylation of both Akt and 4EBP, and increasing the phosphorylation of AMPK. It was also found to affect the subcellular localization of the key components of this signalling pathway. PI3K/Akt pathway was addressed to be an upstream regulator of NF-ĸB pathway. Depleting polyadenylation factors (Cpsf4 and Wdr33) in macrophages was associated with repression of the LPS-induced inflammatory gene expression, reduction in the nuclear localization of p65 and inhibition of PI3K/Akt signalling. This suggests that polyadenylation factors is an upstream regulator of NF-ĸB pathway and PI3K signal transduction pathway. Thus, cordycepin produces its anti-inflammatory effect in macrophages through is effect on polyadenylation. Furthermore, LPS and cordycepin treatment affected the localization of polyadenylation factors, suggesting that polyadenylation machinery is implicated in the inflammatory response. Inhibition of either import of cordycepin into cells or phosphorylation of cordycepin was sufficient to abolish its anti-inflammatory effects. It was found that there is no bioavailable cordycepin in rat’s plasma after oral administration (Lee 2019), 3’deoxyinosine was considered an inactive metabolite. Our results showed that 3’deoxyinosine has anti-inflammatory effect as it repressed the relative mRNA level of the assessed genes (Tnf, Il1b, Acod1 and Ticam) in macrophages.